Antenatal depression and its correlates - a cross-sectional study in an urban resettlement colony of Delhi - Gupta, Bhawna; Mangal, Abha; Thakur, Archana; Vaghela, Joyce Felicia; Sharma, Amita (Indian Journal of Community Health, 2022)
Background- Antenatal depression is affecting 10% pregnant women worldwide with higher prevalence in developing countries. This causes poor maternal and foetal outcome and also affects cognitive development of the child. Aim and objective: To estimate magnitude of antenatal depression and its risk factors. Methodology- A cross-sectional survey was done at the antenatal clinic of community health department catering to an urban resettlement colony, East Delhi. Estimated sample size was 216 (including 10% non-response rate). Pregnant women attending the ANC clinic from October 2019 to February 2020 were enrolled. EPDS questionnaire was used to assess depression during pregnancy. Results-The antenatal depression was found in 11.8% subjects as per EPDS score. Working female and belonging to Muslim religion, past history of abortion, complications in previous pregnancy, financial debt, physical violence and substance use in family showed significant association with antenatal depression. Conclusion –Depression was prevalent among antenatal women and was found to be associated with various risk factors.